1975
DOI: 10.1149/1.2134375
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lead on the Hot Corrosion of Nickel‐Base Alloys

Abstract: Lead is often found as a trace impurity in fuels used in gas turbines. In addition, lead salts may form on hot superalloy parts during turbine operation in contaminated urban environments. An experimental and thermodynamic study of Na2SO4‐normalinduced hot corrosion of nickel‐base alloys at 900°C, in the presence of small concentrations of lead salts, has shown that these contaminants can be very deleterious to alloy corrosion resistance. normalPbO reduces the corrosion resistance of Ni‐Cr and Ni‐Al all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Alkali metals such as potassium and sodium can also attack the protective chromia scale and form the unprotective chromates, potassium chromate and sodium chromate . In addition, it has long been known that lead oxide attacks nickel–chromium alloys and reduces the corrosion resistance by the formation of lead chromate . Lead chloride was more recently found to have a similar effect on stainless steels .…”
Section: Discussionmentioning
confidence: 99%
“…Alkali metals such as potassium and sodium can also attack the protective chromia scale and form the unprotective chromates, potassium chromate and sodium chromate . In addition, it has long been known that lead oxide attacks nickel–chromium alloys and reduces the corrosion resistance by the formation of lead chromate . Lead chloride was more recently found to have a similar effect on stainless steels .…”
Section: Discussionmentioning
confidence: 99%
“…28 Its coefficient of thermal expansion is close to that of carbon steel, leading to lower thermal tensions. 28 It has long been known that lead oxide attacks nickel based alloys and reduces the corrosion resistance by the formation of lead chromate, 29 and it has more recently been shown that alkali metals such as potassium 12 and sodium 13 can also attack the protective chromia scale and form the non-protective chromates, potassium chromate and sodium chromate, as mentioned above. However, our work 30 previously showed that potassium and lead together have been found in the corrosion process.…”
Section: Corrosion Of Alloy In625mentioning
confidence: 99%